INCREASING CREATIVE COMPETENCE OF STUDENTS AND STRENGTHENING EDUCATIONAL EFFICIENCY BASED ON INDIVIDUAL APPROACH (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
On the fundamental principles of forming a competency-based approach in the paradigm of modern education, which allows for the assignment of an important didactic goal to students' independent work.